1999
DOI: 10.1095/biolreprod60.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Stimulates Mouse Blastocyst Outgrowth through a Mechanism Involving Parathyroid Hormone-Related Protein1

Abstract: The goals of this study were 1) to compare the effects of transforming growth factor-beta (TGF-beta) and parathyroid hormone-related protein (PTHrP) on mouse blastocyst attachment and outgrowth in vitro, 2) to determine whether TGF-beta acts through a mechanism involving PTHrP, 3) to examine effects of PTHrP on preimplantation mouse embryo development, and 4) to determine the pattern of expression of PTHrP protein in the uterus of the mouse during early gestation. In the first set of experiments, hatched blast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 52 publications
(67 reference statements)
3
30
1
Order By: Relevance
“…Co-expression of inhibitory Smad 7 indicates the potential for tight regulation of activin/ TGFb action during cleavage and blastocyst development (Zwijsen et al 2000). Exogenous TGFb facilitates embryonic development in vitro, promoting blastocyst proliferation and development and increasing blastocyst cell number (Paria & Dey 1990, Lim et al 1993, Nowak et al 1999 (Fig. 1).…”
Section: Regulation Of Early Embryo Developmentmentioning
confidence: 99%
“…Co-expression of inhibitory Smad 7 indicates the potential for tight regulation of activin/ TGFb action during cleavage and blastocyst development (Zwijsen et al 2000). Exogenous TGFb facilitates embryonic development in vitro, promoting blastocyst proliferation and development and increasing blastocyst cell number (Paria & Dey 1990, Lim et al 1993, Nowak et al 1999 (Fig. 1).…”
Section: Regulation Of Early Embryo Developmentmentioning
confidence: 99%
“…2B). After culturing for 3-4 days, spherical blastocysts became flattened on the culture dish and formed a multicomponent structure in which the inner cell mass grew as a round shape on top of the extra-embryonic trophoblast giant cells (32). In these cultures heterozygous TopBP1 ϩ/⌬ and wild-type embryonic cells normally developed into inner cell mass and trophoblast giant cells.…”
Section: Mefs Suggests That the Topbp1mentioning
confidence: 99%
“…There are indications however that TGF-␤ signaling interferes with extracellular matrix deposition in trophectoderm cells as overexpression of T␤RII in preimplantation embryos was shown to upregulate laminin deposition (Mummery and van den Eijnden-van Raaij, 1999). By contrast, Nowak et al (1999) found a marked increase in the area of trophoblast outgrowths exposed to TGF-␤1. Interestingly, this growth stimulatory effect could be inhibited by simultaneous addition of parathyroid hormone-related peptide (PTHrP) neutralizing antibodies.…”
Section: Tgf-␤ In Trophectodermmentioning
confidence: 74%
“…Interestingly, this growth stimulatory effect could be inhibited by simultaneous addition of parathyroid hormone-related peptide (PTHrP) neutralizing antibodies. Since PTHrP can increase trophoblast outgrowth, these results suggest that in trophoblasts TGF-␤1-induced outgrowth acts by increasing the PTHrP production by the blastocyst (Nowak et al, 1999).…”
Section: Tgf-␤ In Trophectodermmentioning
confidence: 77%